Peran entrepreneurial self-efficacy dalam hubungan digital competence dan opportunity recognition capacity terhadap nascent entrepreneurial behavior - Pratama, Rejas; Purwaamijaya, Btari Mariska; Hermawan, Adam (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2025)
This study addresses the intention–behavior gap in university entrepreneurship by testing how digital competence (DC) and opportunity recognition capacity (ORC) shape nascent entrepreneurial behavior (NEB) through entrepreneurial self-efficacy (ESE). A causal-confirmatory quantitative design was applied to 120 student members of HIPMI PT at Universitas Pendidikan Indonesia; data were analyzed using PLS-SEM (SmartPLS 4). Results show ORC significantly increases ESE and NEB, whereas DC affects only ESE; ESE neither predicts NEB nor mediates the effects of DC and ORC. Theoretically, the findings position ESE as necessary but not sufficient for early entrepreneurial action and identify ORC as a proximal cognitive trigger that channels capability into behavior under supportive conditions. Practically, the study recommends experiential learning and structured opportunity pipelines (e.g., project-based tasks, mentoring/incubation, market validation) to convert self-efficacy into observable nascent behavior.